Validating Migration Responses to Flooding Using Satellite and Vital Registration Data - Chen, Joyce J.; Mueller, Valerie; Jia, Yuanyuan; Tseng, Steven Kuo-Hsin (American Economic Review, 2017)
Rainfall measures may be imperfect proxies for floods, given factors such as upstream water balance, proximity to rivers, and topography. We check the robustness of flooding-migration relationships by combining nationally-representative survey data with measures of flooding derived from weather stations, gridded products, and remote sensing tools. Linear probability models reveal that extreme flooding is negatively associated with out-migration. Rainfall-based proxies produce results qualitatively similar to those using the satellite-based measure of inundation, but only the latter is able to discern non-monotonic effects throughout the distribution. Moreover, estimates differ widely across areas, suggesting that households respond differently to rainfall and flooding.